Musykilat Ta'lim Maharah al-Kalam Li Marhalah al-Jami'ah Lada Thalabah Qism Ta'lim al-Lughah al-'Arabiyah Wa Halluha - Arif Mustofa (Arabiyatuna: Jurnal Bahasa Arab, 2017)
If we speak about language, we know that it has four skills: listening, speaking, reading and writing. But many students are not competent for all skill, although these skills relate to each other. For example, the student could not speak Arabic only by listening and vice versa, as well as the skill of the book and reading, and could not dictate the ability to read. In this research, the researcher focused on teaching speech skills in terms of the problems faced by students at the university stage, especially in the Department of Arabic Language Education. Because the students at the university stage feel the difficulty in speaking in Arabic, although this skill is one of the important skills in the language, because the language is the speech, and sometimes they speak Arabic, but they mixed in the mother tongue compound or single. From this research, the researcher hopes to know the problems and difficulties faced by students of the Department of Arabic language education, especially in the skill of speech and knowledge of solutions that benefit students of the Department of Arabic language education to solve problems and difficulties when learning the skill of speech among university students. In this research, we know that the problems faced by the students of the Department of Arabic Language Education are varied, such as language problems, psychological problems, and practical problems such as lack of vocabulary, fear, shyness, lack of training and training in Arabic speaking outside the classroom. Students are encouraged to speak and to remove the fear of them by showing that all students have the equal opportunity to develop the skill of speech and some are not superior to others.